2017
DOI: 10.1002/nur.21789
|View full text |Cite
|
Sign up to set email alerts
|

African‐American Fathers' Perspectives on Facilitators and Barriers to Father–Son Sexual Health Communication

Abstract: African-American males ages 13 through 24 are disproportionately affected by sexually transmitted infections (STIs) and human immunodeficiency virus (HIV), accounting for over half of all HIV infections in this age group in the United States. Clear communication between African-American parents and their youth about sexual health is associated with higher rates of sexual abstinence, condom use, and intent to delay initiation of sexual intercourse. However, little is known about African-American fathers’ percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Most of the studies on parent–child sexual communication conducted among African American (AA) youth has focused on mother–daughter and mother–son sexual communication ( Kapungu et al, 2010 ; Widman et al, 2016 ), which typically focuses on pregnancy prevention. However, there is a dearth of research examining father–child sexual communication among AA youth ( Harris et al, 2019 ; Randolph et al, 2017 ), and even less exploring the association between this communication and HIV testing ( Boyd et al, 2020 ).…”
mentioning
confidence: 99%
“…Most of the studies on parent–child sexual communication conducted among African American (AA) youth has focused on mother–daughter and mother–son sexual communication ( Kapungu et al, 2010 ; Widman et al, 2016 ), which typically focuses on pregnancy prevention. However, there is a dearth of research examining father–child sexual communication among AA youth ( Harris et al, 2019 ; Randolph et al, 2017 ), and even less exploring the association between this communication and HIV testing ( Boyd et al, 2020 ).…”
mentioning
confidence: 99%
“…Additionally, parents who demonstrated warmth, love, concern, and caring were more likely to have adolescents who practiced abstinence or reduced the number of sexual partners (Aspy et al, 2007). Furthermore, AA fathers believe that it is their responsibility to communicate with their sons (Randolph et al, 2017; Wilson et al, 2010) and that the quality of the father–son relationship could impact parent–son sexual communication. However, despite the relationship quality, AA fathers understood the importance of educating their sons about sex even if the relationship was strained or inconsistent (Baker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies examining familial communication about sex have focused on communication between mothers and daughters [23,29], while less is known about the nature and influence of father–son sexual health communication [34,35]. One recent exception is a qualitative study by Randolph and colleagues (2017), who found that African American fathers perceived that relationship and communication quality would facilitate conversations with their son, while developmental readiness of the child, communication discomfort and not talking to their own fathers about sex when growing up would serve as barriers to such discussions [35]. This study focused on fathers’ perceptions of barriers and facilitators (not necessarily past experiences), and also shared a limitation of other studies in that it did not talk directly to adolescents about their experiences with such conversations.…”
Section: Introductionmentioning
confidence: 99%